2012
DOI: 10.1177/1077559512454216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multidisciplinary Family Treatment Drug Court on Child and Family Outcomes

Abstract: Family treatment drug courts (FTDCs) are an increasingly common approach for serving families involved in child welfare due to parental substance abuse; however, the evidence base for FTDCs remains emergent. This quasi-experimental study replicates previous research on FTDCs by comparing parental substance abuse treatment and child welfare outcomes for 76 FTDC participants to outcomes for 76 parents in the same system who did not participate in the FTDC, using propensity score matching. Data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…Neglect can be prevented or reduced in atrisk families (i.e. : drug-abusing parents) by specific interventions, such as multidisciplinary family treatment drug court [50], parent-child interaction therapy [51,52], family behaviour therapy [53] and personal and family support [54]. Only few specifically designed interventions for neglected children are described in the literature [55] and multisystemic therapy may be a tool for the treatment of both victims and their families [56].…”
Section: Conclusion and Clinical And Future Implicationsmentioning
confidence: 99%
“…Neglect can be prevented or reduced in atrisk families (i.e. : drug-abusing parents) by specific interventions, such as multidisciplinary family treatment drug court [50], parent-child interaction therapy [51,52], family behaviour therapy [53] and personal and family support [54]. Only few specifically designed interventions for neglected children are described in the literature [55] and multisystemic therapy may be a tool for the treatment of both victims and their families [56].…”
Section: Conclusion and Clinical And Future Implicationsmentioning
confidence: 99%
“…As a result of the release of these drugs, in general, resulted in the emergence of organic mental disorders and promiscuity which in turn undermine the future of the nation [3]. favorable outcomes for the whole family [6,7] Advances in Health Science Research, volume 6…”
Section: Drugs (Narcotics and Drugs Containingmentioning
confidence: 99%
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009). To date, long-term outcomes have not been evaluated.…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%